Utilization of dwarf dura mother palms for production of high yielding and dwarf oil palm (Elaeis guineensis) hybrids: Utilization of dwarf dura mother palms for production of high yielding and dwarf oil palm (Elaeis guineensis) hybrids - ANITHA PEDAPATI; RAVI KUMAR MATHUR; G RAVICHANDRAN; B KALYANA BABU; H P BHAGYA (Journal of Oilseeds Research, 2020)
The present investigation was carried out to search for source of high yielding and short stature mother palms in India. We identified palm that has the highest yield of 181.70 kg, more number of bunches (20.50) and less height increment (18 cm) in comparison to other progenies by taking moving average (yield: 98.13 kg, no. of bunches: 13.38, height increment: 32.48 cm) of the same cross. The mesocarp content of this accession also more (72.20%) when compared with the standard duras. Another palm selected (Palm N0: 47) has the highest yield (221.30 kg) and medium height increment (33.00 cm) in comparison to other progenies by taking moving average (yield: 103.77 kg, height increment: 31.81 cm) of the same cross. The utilization of high-yielding genetic base as a planting material has been proven to be the most efficient and sustainable means of increasing the yield output of existing oil palm genetic base. This genetic stock recorded highest yield and short stature compared with other progenies. However, it can be used as a mother parent for the development of high yielding and dwarf oil palm hybrids.